The non-quorum board in a limited liability company - Kawalec, Grzegorz Adam (The Opole Studies in Administration and Law, 2021)
This article presents the issue of a “non-quorum” board in a limited liability company. The discussed commercial law institution was not regulated by the Commercial Companies Code, but was developed by a doctrine. In this article, the author presents typical aspects of the functioning of the management board – company representation and the management of company affairs by the “non-quorum” board. The author analyzes various positions in the doctrine and judicial decisions and endeavours to prove that in order to perform important legal activities in the external and internal sphere of relations in a limited liability company, the right number of board members is important, not the existence of the board itself. In the final part of the work, the author analyzes the role of a probation officer in the company in terms of his powers related to managing the company’s affairs and representing it.